Pencak Silat Aliran Sang Maung Bodas: Refleksi Etika, Spiritualitas, dan Identitas Budaya dalam Tradisi Sunda dan Pesantren - Yusep Saepulloh; Rudi Ripandi; Moch Mumin Amirulloh (Jurnal Dirosah Islamiyah, 2026)
This study investigates the symbiosis between the practice of Pencak Silat Aliran Sang Maung Bodas and a holistic pedagogical framework known as the concept of ‘Five Of’ (To guard, to protect, to guard, to guard, to protect). This model, developed by the Dzikir Al-Fath Modern Islamic Boarding School, is intended to respond to contemporary challenges in the form of a crisis of moral integrity and the high rate of educated unemployment or "intellectual unemployment" amidst the pace of modernization. This study uses a qualitative, descriptive ethnographic approach, located in Sukabumi, West Java, by applying in-depth interviews, passive-participatory observation, and documentation analysis to uncover cultural meanings (perspectivesemic). The findings indicate that the framework ‘Five ofeffectively reflect EthicsSantripreneur, whereWatchemphasize independence in the economic field andProtectdemanding competencesurvival. The combination of these two values seeks to instill a spirit of independence and an ethoswork plan (work hard), while facilitating the achievement excellent science (higher knowledge). The spiritual dimension is internalized through valuesWait, which is a spiritualized practice of physical discipline. This method requires its implementation to be accompanied by dhikr (remembrance of God) in every movement, thus deeply reflecting the Sundanese philosophy ofEmpty-Content. This philosophy of duality acts as an ethical regulatory mechanism, guiding the emptying of oneself from selfish desires in order to mitigate arrogance (arrogant) and facilitate the achievement of spiritual maturity (Perfect ManFurthermore, Paguron Silat Sang Maung Bodas functions as a symbolic system that strengthens Sundanese Cultural Identity, supported by the historical legitimacy of Pajajaran heritage and cultural values.Reciting the Koran(namely the strengthener of his religion) andguard (cosmic harmony).